Bioactive glasses and glass-ceramics : fundamentals and applications - Baino, Francesco; Kargozar, Saeid (John Wiley & Sons, Inc., 2022)
"The goal of this book is to cover all the major aspects relevant to bioactive glasses and glass-ceramics, including their functional properties, processing and applications. Special focus is given to the current clinical applications and market needs, as well as to the challenges deserving to be tackled in the near future. The book is a valuable source to both early-stage researchers, who are moving with their first steps in the world of bioactive glasses, and experienced scientists from university and industry, thereby stimulating discussion about future research and new applications for glass in medicine. Overall, the book aims to (i) describe the main classes of bioactive glasses and glass-ceramics, providing the fundamentals of their synthesis, processing and properties; (ii) provide an overview of clinical applications and existing commercial products, discussing the limitations and unmet needs; (iii) outline the challenges to improve performance and the directions that novel approaches are taking to meet these challenges"-- Provided by publisher.
Keywords: Bioactive glasses.; Glass-ceramics.; Glass in medicine.; Bioactive glasses -- Therapeutic use.; Glass-ceramics -- Therapeutic use.; elektronické knihy; electronic books